Precedent Anthroponyms of Soviet Origin in English Polycode Advertising Text - E. V. Dziuba; Yu. V. Rogozinnikova (Научный диалог)
The article analyzes precedent anthroponyms of the Soviet origin in multimodal texts of American and British advertising. The study aims at analyzing precedent anthroponyms of the Soviet origin in English multimodal texts from the linguoaxiological and linguopragmatic points of view and from the standpoint of textual organization. The following research methods have been used: description and synthesis, linguistic methods of structural-semantic, contextual and cognitive-discourse analysis. The paper examines the precedent names of the Soviet origin (for instance, Lenin, Stalin, Brezhnev, Gorbachev, Yeltsin, and Kalashnikov). It also establishes their uses in commercial texts and highlights the linguistic means of satirical effect creation as the main pragmatic goal of English commercial and social advertising. The name of a political leader acquires different connotations and in most cases it is “demoted” due to the transfer of the name from the political context to the everyday one: gastronomic, material, kitsch-cultural, glamorous-erotic, etc. Names of the Soviet politicians are found in advertisements of cigarettes, pizza, alcoholic and nonalcoholic drinks, bags and other household items, including absorbent wipes. The article concludes that the image of the Soviet past in multimodal advertising texts in English acquires negative connotations. Besides, the analyzed texts emphasize that the communist ideology belongs to the system of anti-values.